THE SPRING RESORT CAPITAL OF THE PHILIPPINES: TOURISM PRODUCT PREFERENCES AND THE PROFICIENCY LEVEL OF THE LOCAL COMMUNITY - Aguilar, Mark Gabriel (Politeknik Pariwisata NHI Bandung, 2023)
Understanding the market and having a competent workforce are two very important aspects in the field of tourism and hospitality business to ensure sustainability, especially in places where the industry is seen to be a primary source of development. Guided by a descriptive research design and following a quantitative research approach, A total of 770 people took part in the survey, which covered the whole province of Laguna, Philippines, this study has attempted to learn about the market’s preferences on tourism products and to measure the proficiency level of a local community in the Philippines towards tourism and hospitality operations. Findings of this study is expected to help the government and tourism businesses, as well as investors in designing products and services that would sell, eventually resulting in the viability of the industry